Why academics should study the supply chains of individual corporations. (19th September 2019) - Goldstein, Benjamin; Newell, Joshua P.
Abstract: Although fields such as industrial ecology have advanced our understanding of how cleaner technologies, recycling, and lifestyle changes can reduce the impacts of production and consumption on people and planet, environmental deterioration and social injustices stubbornly persist. New strategies are needed to achieve change in an era of increasing urgency. This paper proposes that academics study the supply chains of individual corporations and link them to environmental and social impacts in geographically specific areas. Nongovernmental organizations (NGOs) have used this approach successfully, issuing reports about corporate activity related to deforestation, sweatshops, and other issues of social concern. But academics, by and large, have studied generic products, industries, and sectors. To verify this, after reviewing approximately 11, 000 studies on supply chains, we identified just 27 academic papers that focused on individual corporations. These were primarily by NGOs and social scientists, with no studies by industrial ecologists meeting our review criteria. To uncover corporate supply chains, researchers used two distinct methodological approaches: in situ (interviews, surveys, and surveillance) and ex situ (trade data, document analysis, and maps). In this paper, we explain why and how academics should study the supply chains of individual corporations. This is done by combining approaches from industrial ecology, with those from geography, sociology, and other social sciences to develop a political‐industrial ecology of supply chains. This both physically links actual product flows with their environmental impacts, and explores how they affect justice, equity, and welfare. The work we propose offers clear collaborative linkages with NGOs, industry, and the media.